STRATEGI PEMBANGUNAN ILMU PENGETAHUAN, TEKNOLOGI DAN INOVASI DAERAH DI SULAWESI TENGGARA - Syamsul Alam; Faturachman Al Putra; La Ode Mustafa R (Journal Publicuho, 2022)
The purpose of this study is to describe the general conditions of regional science, technology and innovation (Iptekin) development, analyze opportunities and threats in the external environment as well as strengths and weaknesses in the internal environment, and formulate a strategic goals and objectives for the development of effective regional Iptekin in Southeast Sulawesi. This research uses a qualitative approach with an interpretive perspective. Data collection techniques used include interviews, document studies, benchmarking, and focus group discussions. Qualitative data analysis of the interactive model found that regional Iptekin development in Southeast Sulawesi is characterized by weak institutional and social and organizational fragmentation, and lack of resources. The overall factors of the political, economic, social, technological and legal environment contain opportunities and threats to the development of regional Iptekin but the dominant one is from the political environment. The factor of creating public value and assets/inventory are both internal strengths and weaknesses for the development of regional Iptekin. The strategic objective of regional Iptekin development based on environmental assessment is to increase the capacity of science and technology and the effectiveness of the implementation and utilization of regional science and technology.